Akselerasi covid-19 pada proses pembelajaran di era pendidikan 4.0 - Fathirma’ruf Fathirma’ruf; M. Nur Imansyah; Asmedy Asmedy (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The development of technology in the world of education has given rise to a new paradigm of learning and teaching, which was previously carried out conventionally by switching to the use of information technology, Limited means and use of technology have become an important issue in meeting the demands of education in the 4.0 era, since the Schwab Clause and the World Economic Forum declared Fourth Industrial Revolution, since then technology has penetrated into the world of education, but in fact educators at several educational institutions until before the Covid-19 Pandemic were still reluctant to use technology as an effective teaching and learning tool. This research is a descriptive study that aims to summarize related to the facts that occur in the learning process in the Covid-19 pandemic situation. The transfer of the learning process to online mode forces all parties to take part in ensuring the continuity of learning during the pandemic, including the Government. Here, the Ministry of Education and Culture provides support through help and policy in supporting the learning process; besides that, technology provides for education also takes part in improving their technology services to learn for educators and students; as well as educational institutions, practitioners, teachers, and lecturers to respond positively to this support by increasing individual competence and making the best use of these learning tools.